Grenada : Interim Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper discusses the Interim Poverty Reduction Strategy Paper (I-PRSP) of Grenada for poverty reduction in the interim period. It describes the country's macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. It reviews the National Poverty Eradication Strategy and analyzes the monitoring indicators, risks and costing of the strategy. It assesses the national development plan aimed at attaining the Millennium Development Goals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet